Assessment of annual variability in the population status and reproductive cycle of purple sea urchins (Heliocidaris crassispina, Agassiz, 1864) in Daya Bay, China - Zhao, Xinye; Mu, Xiaohui; Guo, Yu; Li, Jiayang; Ma, Zhenhua; Yu, Gang; Qin, Chuanxin (Frontiers in Marine Science, 2024)
The purple sea urchin (Heliocidaris crassispina) is one of the main drivers of ecosystem dynamics, and its reproductive cycle plays an important role in population structure and size variability. In this study, we analyzed the population structure, gonadal developmental characteristics, reproductive cycle and other factors influencing wild purple sea urchins from December 2021 to November 2022 in Daya Bay, Guangdong, China. The results showed that purple sea urchins showed an allometric growth pattern, there were obvious seasonal variations in the population size, and fishing pressure reduced the sea urchin populations; two-factor analysis of variance (ANOVA) and correlation analyses showed negative correlations between month (M), test diameter (TD), weight (W) and gonadal index (GI) (P> 0.01), and a positive correlation between TD, weight (W), and GI (P<0.01); the gonadal development process can be divided into recovery, growth, prematuration, maturation, and late discharge, with almost synchronous development of male and female gametes; the spawning period is from April to November, which is longer than in the temperate zones, showing two spawning peaks in April and August. The time of spawning is influenced by temperature and food. Data on the breeding cycle of sea urchins in Daya Bay were obtained in this study. This information can offer theoretical assistance in the preservation and management of both artificial nurseries and wild resources.